Exploring the Factor and Cluster of Green Building Practices for Urban Liveability: Case Study Jakarta, Indonesia - Suhardono, Sapta; Septiariva, Iva Yenis; Sianipar, Imelda Masni Juniaty; Suryawan, I Wayan Koko (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
This study investigates the multifaceted landscape of green building practices, focusing on their factor structure and cluster characteristics concerning environmental responsibility and urban livability. A comprehensive analysis identifies distinct factors and clusters, each representing different dimensions of sustainable urban development. This study embarks on an exploration of the complex domain of green building practices, employing Exploratory Factor Analysis (EFA) and k-means clustering to dissect the factor structure and clustering characteristics pertinent to environmental responsibility and urban liability. The factors encompass environmental sustainability and urban convenience, highlighting the delicate balance between ecological consciousness and urban functionality. Delving into demographic variables like income, higher education, age, and marital status, our findings reveal statistically significant correlations, emphasizing the pivotal role these individual characteristics play in shaping preferences towards green building practices. Specifically, our analysis crystallizes into two primary clusters. Cluster 1 emphasizes the essence of "Environmental Sustainability," marked by a strong inclination towards energy efficiency, sustainable materials, and green spaces, reflecting a commitment to ecological stewardship. In contrast, Cluster 2, denoting "Urban Convenience and Access," underscores the importance of proximity to public transport, shopping centres, and workplaces, encapsulating a desire for accessibility and convenience in urban design.